Pengembangan Mi Bebas Gluten dengan Teknologi Ekstrusi - Mojiono, Mojiono; Nurtama, Budi; Budijanto, Slamet (Perum BULOG, 2016)
Diversifications of raw materials for noodle preparation using local carbohydrate sources offer considerable advantages through lowering wheat demand and providing specially-designed food such as gluten-free diet. Structural formations of gluten-free noodles substantially differ from wheat-based noodles due to the presence of gluten. Therefore, studies on starch characteristics including the ratio of amylose and amylopectin, granule morphology, and gelatinization properties are absolutely essential since they are responsible for noodle quality. Starch modification, for instance, HMT (heat moisture treatment), is a promising technique to improve starch properties for noodle preparation. Furthermore, processing conditions also account for noodle quality. Extrusions constitute an appropriate technology for the development of noodle processing technique as it gelatinizes starch and produces pressing and kneading effects that are required to form desirable noodle structure. This paper reviews current studies of gluten-free noodles and extrusion technology for noodle production.